1997
DOI: 10.5144/0256-4947.1997.185
|View full text |Cite
|
Sign up to set email alerts
|

Trihexyphenidyl (Artane) Dependence: A Controlled Investigation between Users and Abusers

Abstract: This controlled study aims to identify the socioclinical factors predisposing psychiatric patients to abuse trihexyphenidyl (artane) and to document the extrapyramidal symptoms in artane abusers and users. Thirty patients (n=30), with mainly two major functional psychoses and who were abusing trihexyphenidyl, were compared with 90 artane user patients (n=90), who were matched for both the diagnosis and treatment. Besides a detailed clinical interview, each patient was assessed by using DSM-IIIR criteria, Brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…In our two studies of psychiatric patients with trihexiphenidyl abuse, a similar pattern of smoking was also found 36,37…”
Section: Discussionsupporting
confidence: 78%
“…In our two studies of psychiatric patients with trihexiphenidyl abuse, a similar pattern of smoking was also found 36,37…”
Section: Discussionsupporting
confidence: 78%
“…Schizophrenia is the commonest axis I diagnosis among THP abusers in this study but has no signifi cant relationship with THP misuse as reported in other studies elsewhere [20].…”
Section: Discussioncontrasting
confidence: 54%
“…Abuse potential of the THP and other anticholinergice calls for caution in its prescription amidst other disadvantages. Easy availability, affordability and indiscriminate prescription will give serendipitous patients suffi cient time to realise the euphorigenic and addictive potentials of THP [20]. Anticholinergics should be tailed off after initial prescription of about 3-months to ease gradual cessation.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In contrast, in the rapidly developing Arabian Gulf countries, the literature on smoking in the general population is relatively scanty. In two studies of trihexyphenidyl abuse, 17,18 we found that 85.7% and 90% of studied patients were cigarette smokers. The main objectives of our study were: 1) to examine the probable prevalence and pattern of smoking among male psychiatric outpatients; and 2) to investigate the sociodemographic variables between smokers and nonsmokers.…”
mentioning
confidence: 99%